A CORPUS-BASED ANALYSIS OF ENGLISH PAST PERFECT TENSE IN WRITTEN AND SPOKEN ENGLISH - Budi Putra Johan, Surya (PEOPLE: International Journal of Social Sciences, 2017)
The ability to use English past perfect tense in different functions such as setting a background information, or explaining cause-effect relationship is an important aspect of language use. This research paper focuses on the different functions of past perfect tense in academic writing and speaking. The Corpus of Contemporary American English (COCA) was used for an analysis of the functional patterns of past perfect tense in different functions. A combination of both quantitative and qualitative research techniques was used during the research. Based on the corpus data, the top two patterns of past perfect tense have been mainly used – to set background information, and to provide reason/cause. The function of providing (or setting) the background information is further analyzed into seven sub-functions. It is hoped that the corpus findings can be applied in language teaching so that language learners can discover language rules based on corpus data.